Improving Children's Cognitive Skills Through Project-Based Science Hydroponic Planting - Nurul Hazma; Noor Baiti; Herman Taufik; Uswatun Nisa (CV. Edujavare Publishing, 2025)
This research is motivated by the importance of developing early childhood cognitive abilities through engaging and meaningful learning experiences. The aim of this study is to enhance children's cognitive skills through science-based hydroponic planting projects at Handayani Kindergarten, Awang Bangkal Barat Village. The method used is Research and Development (R&D), consisting of the stages of design, validation, revision, and limited implementation. The research subjects are children aged 5–6 years. Data collection techniques include observation, interviews, and questionnaires, while data analysis employs both quantitative and qualitative descriptive analysis. The results show that the developed hydroponic learning media received a feasibility score of 100% from material and media experts, categorized as highly feasible, and a practicality score of 85% from teachers, categorized as very good. Furthermore, the use of this media is able to improve children's cognitive abilities, particularly in observation, logical thinking, and drawing simple conclusions. Therefore, science learning based on hydroponic planting projects is effective in enhancing the cognitive abilities of early childhood learners